Heterologous prime-boost vaccination drives stromal activation and adaptive immunity against SARS-CoV-2 variants - Jeon, Ji Hyang; Kim, Seongryong; Kim, Seo-Yeon; Shin, Kwang-Soo; Park, Bongju; Chang, Soojeong; Kang, Chang-Yuil; Kim, You-Jin; Park, Jong-Eun; Youk, Sungsu; Kim, Dokeun; Yeo, Jinah (Frontiers in Immunology, 2025)
Heterologous vaccination strategies have shown superior efficacy over homologous regimens in clinical studies, but the underlying immunological mechanisms remain incompletely understood. Using a mouse model, we investigated the immune responses induced by heterologous prime-boost vaccination with adenoviral and mRNA vaccines. Heterologous vaccination (adenoviral prime, mRNA boost) elicited higher neutralizing antibody titers and stronger CD8+ T cell responses against Delta and Omicron-BA.5 variants compared to homologous regimens. Single-cell transcriptomic analysis of injection-site tissues revealed that adenoviral priming induced minimal changes in cellular composition but established a pre-conditioned innate immune environment. This effect was further amplified upon mRNA boosting, particularly through fibroblast-driven chemokine responses that promoted immune cell recruitment. These findings suggest that adenoviral priming enhances local immune activation upon boosting, contributing to the heightened adaptive immune response observed in heterologous vaccination. This study provides mechanistic insights into the immunological effects of heterologous prime-boost strategies against SARS-CoV-2 variants.